Improving the Ability to Sing Folk Songs through the "Project Based Learning" Model assisted by "Audio Song Program" Media - Sugeng Wiyono (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to improve the essential ability of singing in students. This fact was obtained before this research was conducted; the ability of students to sing folk songs still needs to be improved, as evidenced by the value of the ability to learn to sing the students of class VIII F SMP Negeri 2 Tempuran is not optimal. This research was conducted using a class action research method consisting of two cycles. In cycle I, indicator A (Vocal Material), the average score obtained was 72.4; in cycle II, the average score obtained was 78.0. Indicator B (Intonation) In the process I, the average score obtained was 73.2, and in cycle II, the average score obtained was 78.8, indicator C (Phrasing) cycle I, the score obtained was 72.5, while in cycle II, the score obtained was 77.5. In process I indicator D (Articulation), the average score obtained was 73.5, and in cycle II was 77.7. Indicator E (Expression) At the time of the process, the average score obtained was 72.5, while in cycle II, the score obtained was 78.2. Behavioral changes also increased. Active students In the process I, there were nine students; in cycle II grew, there were 19 students. In creative Students cycle I, there was seven students; in cycle II increased, there were 20 students. Discipline students in process I; there were ten students; in cycle II grew, there were 18 students.